2017
DOI: 10.4149/gpb_2016021
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial hyperpolarization and cytochrome-c release in microwave-exposed MCF-7 cells

Abstract: This study examines the effects of a 2.1-GHz WCDMA-modulated microwave (MW) radiation on apoptotic activity and mitochondrial membrane potential (ΔΨm) in MCF-7 cells. The cells were exposed to the MW at a specific absorption rate (SAR) of 0.528 W/kg for 4 or 24 h. The antiproliferative effect of MW exposure was determined by the MTT test. Cytochrome-c and p53 levels were determined by an ELISA method. The relative ΔΨm was analysed by JC-1 staining using flow cytometer. Apoptotic rate of the cells was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Mitochondria play pivotal roles in maintaining energy metabolism, and mitochondrial dysfunctions are always associated with neurological damages, including non-infectious stimuli induced injuries 1 3 . Studies from our group and others demonstrated that microwave exposure, a type of electromagnetic radiation, could induce mitochondrial function disorder and mitochondrial structural injuries 4 7 . Interestingly, hypoxia-inducible factor-1α (HIF-1α), a key physiological sensor of oxygen level in most mammalian cells, was up-regulated in PC12 derived neuron-like cells after 30 mW/cm 2 microwave exposure.…”
Section: Introductionmentioning
confidence: 81%
“…Mitochondria play pivotal roles in maintaining energy metabolism, and mitochondrial dysfunctions are always associated with neurological damages, including non-infectious stimuli induced injuries 1 3 . Studies from our group and others demonstrated that microwave exposure, a type of electromagnetic radiation, could induce mitochondrial function disorder and mitochondrial structural injuries 4 7 . Interestingly, hypoxia-inducible factor-1α (HIF-1α), a key physiological sensor of oxygen level in most mammalian cells, was up-regulated in PC12 derived neuron-like cells after 30 mW/cm 2 microwave exposure.…”
Section: Introductionmentioning
confidence: 81%
“…The known risk factors for breast cancer are obesity (8), smoking (9), genetic mutations such as breast cancer susceptibility gene 1 (BRCA1) and breast cancer susceptibility gene2 (BRCA2) which are tumor suppressor genes (9,10), family history (11,12), alcohol consumption (11)(12)(13)(14), exposure to estrogen hormones over an extended period (11,14), diethylstilbestrol and postmenopausal hormone therapy (15,16). In addition, previous studies suggested that breast cancer can be attributed to exposure to radiofrequency radiation (17,18). Experimental research has demonstrated that simulated radiofrequency radiation exposure can cause damage to human breast cancer MCF-7 cells and promote the formation of reactive oxygen species (ROS), which are the primary cause of DNA strand breaks and cell death (17,18).…”
Section: Exposure To Radiofrequency Radiation Increases the Risk Of Bmentioning
confidence: 99%
“…In addition, previous studies suggested that breast cancer can be attributed to exposure to radiofrequency radiation (17,18). Experimental research has demonstrated that simulated radiofrequency radiation exposure can cause damage to human breast cancer MCF-7 cells and promote the formation of reactive oxygen species (ROS), which are the primary cause of DNA strand breaks and cell death (17,18). Cigand Naziroglu (17) indicated that exposure of breast cancer cells to radiofrequency radiation was associated with the accumulation of ROS and disruption of mitochondrial membrane pores, which resulted in swelling and dysfunction of mitochondria, causing rupture of the outer membranes and the release of apoptosis-inducing factors.…”
Section: Exposure To Radiofrequency Radiation Increases the Risk Of Bmentioning
confidence: 99%
“…Smartphone-emitted radiofrequency radiation induces the creation of ROS, which contribute to DNA mutations and carcinogenesis. 13 Circadian disruption results in the inhibition and delay of melatonin expression, 17 consequently decreasing the quality of sleep and benefiting the release of estrogen, which promotes the development of breast cancer. 45 47 …”
Section: Discussionmentioning
confidence: 99%
“…1 Radiofrequency radiation emitted by smartphones is thought to be associated with greater concerns about health risks and cancer-related issues. 7 12 It was found that radiofrequency radiation exposure caused mammary cell damage and reactive oxygen species (ROS) formation, 13 , 14 which are the primary causes of DNA strand breaks that can lead to cell death. 12 , 15 Also, it was reported that as smartphones emit light, they can suppress melatonin production, a sleep-promoting hormone.…”
Section: Introductionmentioning
confidence: 99%